BUILDING TRUST THROUGH SERVICES QUALITY AND BRAND IMAGE TOWARDS DECISION IN CHOOSING FINANCIAL INSTITUTION AT PT. SUMMIT OTO FINANCE (CASE STUDY PT. SUMMIT OTO FINANCE KEDOYA BRANCH, WEST JAKARTA) - M. Rizky Mahaputra (Dinasti International Journal of Education Management And Social Science, 2020)
This research aims to explored and analyzed those impact which relate to service quality and brand image in building trust and the decision to choose Oto Finance as financing institution used. The population were customers from PT. Summit OTO Finance which amounted to 9,302 customers until 2019, while the sample amounted to 155 respondents. The analysis technique that used in this research was Structural Equation Modeling (SEM) by Lisrel software. The results showed that: 1) There had partially positive and significant influence from service quality variables on trust; 2) There had partially positive and significant influence of the brand image variable on trust; 3) There had partially positive and significant impact of service quality on decision to choose; 4) There had partially positive and significant influence from brand image variable on decision to choose ; and 5) There had positive and significant influence from the trust variable on decision to choose.